Investigação da ritmicidade circadiana e dos efeitos da privação de sono paradoxal na resposta dos sistemas MCHérgico e Orexinérgico - Martins, Ana Luiza Dias Abdo Agamme [UNIFESP] (2019)
Introduction: Melanin concentrating hormone (MCH) and Orexin are neuropeptides synthesized in distinct groups of neurons of the lateral hypothalamic area that act in a reciprocal way in the regulation of sleep/wake states. MCH induces sleep, mainly paradoxical sleep while orexin induces sleep to wake transitions. Both groups of neurons send difuse projections through the central nervous system (CNS) and their receptors mRNA are distributed in the same cerebral areas, including frontal cortex and hippocampus. These neurons receive projections from the Suprachiasmatic Nucleus (SCN), the main circadian oscillator in mammals. Circadian rhythms in the SCN are generated by a transcription/translation feedback loop involving negative and positive components. Objective: To verify if MCHergic and orexinergic systems presents circadian rhythmicity and if this possible variation is altered by sleep deprivation. Methods: 96 male Wistar rats were distributed into two groups: control condition (CTL; normal sleep) and sleep deprivation for 96 h (SD) in six different moments of the day (ZTs: 0, 4, 8, 12, 16 and 20). We analyzed cerebrospinal fluid (CSF) MCH and orexin levels, expression of Pmch and Hcrt gene in the hypothalamus, and the expression of Mchr1 and Hcrtr1 gene in the frontal cortex and hippocampus and Hcrtr2 in the hippocampus. We also verified the expression of clock genes (Clock, Bmal1, Per1, Per2, Cry1 and Cry2) in the same experimental conditions to test whether SD modifies diurnal variation of clock genes expression in the hypothalamus. Results: MCH and orexin do not present diurnal variation in the CSF of CTL animals. In the SD group, we verified higher levels of MCH in the beginning of the dark phase. Pmch and Hcrt gene expression do not present diurnal variation in the hypothalamus in both CTL and PS groups. In the frontal cortex, we verified diurnal variation in the expression of Mchr1 and Hcrtr1 only in CTL animals. Concerning clock genes expression, only Per2 and Cry1 presented diurnal variation in their expression in the hypothalamus of CTL rats with a peak of expression in the beginning of the dark phase. This variation was not present in the group. Conclusions: There is diurnal variation in the expression of MCHergic and orexinergic systems and this variation is affected by sleep deprivation. Molecular changes induced by sleep deprivation also affected diurnal variation of clock genes expression. These alterations must be considered when sleep deprivation is used in experimental designs and sleep deprivation consequences were considered.